Early evidence of beneficial and protective effects of Protectin DX treatment on behavior responses and type-1 diabetes mellitus related-parameters: A non-clinical approach - Waltrick, Ana Paula Farias; Radulski, Débora Rasec; de Oliveira, Kauê Marcel; Acco, Alexandra; Verri, Waldiceu Aparecido; da Cunha, Joice Maria; Zanoveli, Janaina Menezes (Progress in neuro-psychopharmacology & biological psychiatry, 2024)
Protectin DX (PDX), a specialized pro-resolving lipid mediator, presents potential therapeutic applications across various medical conditions due to its anti-inflammatory and antioxidant properties. Since type-1 diabetes mellitus (T1DM) is a disease with an inflammatory and oxidative profile, exploring the use of PDX in addressing T1DM and its associated comorbidities, including diabetic neuropathic pain, depression, and anxiety becomes urgent. Thus, in the current study, after 2 weeks of T1DM induction with streptozotocin (60 mg/kg) in Wistar rats, PDX (1, 3, and 10 ng/animal; i.p. injection of 200 μl/animal) was administered specifically on days 14, 15, 18, 21, 24, and 27 after T1DM induction. We investigated the PDX's effectiveness in alleviating neuropathic pain (mechanical allodynia; experiment 1), anxiety-like and depressive-like behaviors (experiment 2). Also, we studied whether the PDX treatment would induce antioxidant effects in the blood plasma, hippocampus, and prefrontal cortex (experiment 3), brain areas involved in the modulation of emotions. For evaluating mechanical allodynia, animals were repeatedly submitted to the Von Frey test; while for studying anxiety-like responses, animals were submitted to the elevated plus maze (day 26) and open field (day 28) tests. To analyze depressive-like behaviors, the animals were tested in the modified forced swimming test (day 28) immediately after the open field test. Our data demonstrated that PDX consistently increased the mechanical threshold throughout the study at the two highest doses, indicative of antinociceptive effect. Concerning depressive-like and anxiety-like behavior, all PDX doses effectively prevented these behaviors when compared to vehicle-treated T1DM rats. The PDX treatment significantly protected against the increased oxidative stress parameters in blood plasma and in hippocampus and prefrontal cortex. Interestingly, treated animals presented improvement on diabetes-related parameters by promoting weight gain and reducing hyperglycemia in T1DM rats. These findings suggest that PDX improved diabetic neuropathic pain, and induced antidepressant-like and anxiolytic-like effects, in addition to improving parameters related to the diabetic condition. It is worth noting that PDX also presented a protective action demonstrated by its antioxidant effects. To conclude, our findings suggest PDX treatment may be a promising candidate for improving the diabetic condition per se along with highly disabling comorbidities such as diabetic neuropathic pain and emotional disturbances associated with T1DM. [Display omitted] •Protectin DX induced antinociceptive effect in diabetic rats.•Protectin DX improved weight gain and glycemic index of diabetic rats.•Protectin DX prevented anxiety-like behavior in rats with diabetes.•Protectin DX prevented depressive-like behavior in rats with diabetes.•Protectin DX reduced oxidative stress parameters in rats with diabetes.